Autonomy and History: How a Desire Becomes One’s Own - Weimer, Steven (Journal of moral philosophy, 2014)
A common view among autonomy theorists is that a desire is autonomous only if it has the right sort of history. Usually, an autonomy-compatible history is taken to consist in the desire’s having had proper origins. In a recent article in this journal, Mikhail Valdman has proposed an alternative historical theory on which a desire’s origins are irrelevant. On Valdman’s “agent-engagement” theory, a desire is autonomous if and only if the agent has made it her own by deliberatively deciding it is worth maintaining and acting on. I argue that both of these approaches are overly demanding: the history of many autonomous desires lack proper origins, agent-engagement, or both. Taking as my starting point Alfred Mele’s account, which I go on to revise and supplement in several important ways, I outline a more flexible historical theory of autonomy which recognizes multiple ways in which a desire can become one’s own.